2016
DOI: 10.21037/jtd.2016.06.46
|View full text |Cite
|
Sign up to set email alerts
|

Misuse of statistics in surgical literature

Abstract: Statistical analyses are a key part of biomedical research. Traditionally surgical research has relied upon a few statistical methods for evaluation and interpretation of data to improve clinical practice.As research methods have increased in both rigor and complexity, statistical analyses and interpretation have fallen behind. Some evidence suggests that surgical research studies are being designed and analyzed improperly given the specific study question. The goal of this article is to discuss the complexiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In reality, clinicians and medical students show unsatisfactory knowledge in Biostatistics and poor ability to apply its concepts in medical research [13]. This leads to difficulty in understanding the statistics of published articles and medical guidelines and reduce their ability to critically appraised literature [10,14]. In a study by Gore et al, results showed that only 2.9% of participants -including faculty members and final year postgraduates -gave the correct meaning of p-value and more than three quarters of participants asked for help of a biostatistician to present their data [15].…”
Section: Introductionmentioning
confidence: 99%
“…In reality, clinicians and medical students show unsatisfactory knowledge in Biostatistics and poor ability to apply its concepts in medical research [13]. This leads to difficulty in understanding the statistics of published articles and medical guidelines and reduce their ability to critically appraised literature [10,14]. In a study by Gore et al, results showed that only 2.9% of participants -including faculty members and final year postgraduates -gave the correct meaning of p-value and more than three quarters of participants asked for help of a biostatistician to present their data [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is incumbent upon medical researchers to understand statistical analysis and properly design an analysis because as many as 78% surgical publications contain significant statistical errors. 4,5 When examining the differences in patients' baseline characteristics, we noted differences that were significant. However, after we examined the distribution of preoperative functional class, and American Society of Anesthesiology class (ASA) scores, the groups were found to be distributed similarly with no statistically significant difference between the specialties leading us to conclude that these differences were not clinically applicable or significant.…”
mentioning
confidence: 96%